The relevance of Quistclose trust in corporate insolvency for the benefit of a non-lending third party - Hingun, Mohsin (2015)
Although the incidence of Quistclose trusts in case law is not a common occurrence, the interest it has spawned among judges and commentators in common law jurisdictions is legion and has been claimed ‘to represent the single most single most important application of equitable principles in commercial life.’79 The nature of the Quistclose trust raises a number of legal challenges: whether it is an express or a resulting trust, whether there is a combination of a primary and a secondary trust, does it comply with the beneficiary principle as an express trust and whether a third party designated by the payer-beneficiary can take advantage of the trust. Recently the Malaysian courts at all levels in PECD Sdn Bhd v Amtrustees Bhd80 had the opportunity to consider the position of a designated third party and they have positively endorsed the view that he can benefit under the primary trust. The objective of this paper is to assess the legal principles in the application of Quistclose trusts, critically analyse the judgment of the Federal Court in PECD Sdn Bhd and offer alternative solutions to the issue raised by the case. The paper adopts a comparative study and doctrinal analysis of relevant decisions clarifying important issues in relation to the use of the Quistclose trust in commercial transactions. It clarifies the appropriateness of applying a Quistclose trust to the commercial arrangements inherent in PECD Sdn Bhd and suggests the availability of alternative remedies.